2022
DOI: 10.1109/ojies.2022.3160095
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Induced Shoot-Through in BTI-Stressed Symmetrical & Asymmetrical Double-Trench SiC Power MOSFETs

Abstract: In this paper, the crosstalk-induced shoot-through current and induced gate voltage of SiC planar MOSFETs, SiC symmetrical double-trench MOSFETs and SiC asymmetrical double-trench MOSFETs is investigated on a half-bridge circuit to analyse the impact of temperature, drain-source voltage switching rate, gate resistance and load current level on crosstalk-induced properties of different SiC MOSFET structures. It shows that due to the smaller gate-source capacitance, the two double-trench MOSFETs exhibit higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Even though these different structured power MOSFETs could have similar ratings as given in the datasheet, their performance would differ under the same operating conditions. It is previously shown that the thermal behaviour of these three different structured MOSFETs are distinct in terms of observed case temperature under repetitive crosstalk events with continuous occurrence of shoot-through in [22]- [24]. The thermal image of each MOSFET structure at its peak case temperature is shown in Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Even though these different structured power MOSFETs could have similar ratings as given in the datasheet, their performance would differ under the same operating conditions. It is previously shown that the thermal behaviour of these three different structured MOSFETs are distinct in terms of observed case temperature under repetitive crosstalk events with continuous occurrence of shoot-through in [22]- [24]. The thermal image of each MOSFET structure at its peak case temperature is shown in Fig.…”
Section: Introductionmentioning
confidence: 92%
“…The devices under test (DUTs) are Rohm's planar SiC MOSFET, symmetrical SiC MOSFET, and Infineon's asymmetrical SiC MOSFET with same voltage rating and similar current rating. Detailed device parameters are shown in Table 978-1-6654-8814-3/22/$31.00 ©2022 IEEE 1, and the structures of three devices are illustrated in [11]. In repetitive SC events, the DUTs are tested at room temperature.…”
Section: A Experiments Setupmentioning
confidence: 99%
“…Since electrons would be released from interface traps in negative gate stressing, this would increase the carrier-carrier scattering level which is the main mechanism that leads to carrier mobility degradation. This inturn impacts the severity of potential crosstalk [17,18] as well. Fig.…”
Section: Negative DC Bias Stressmentioning
confidence: 99%